Immunohistochemical detection of gonadotropin-releasing hormone (GnRH) in porcupine (Hystrix cristata) pancreas - Tarakcl, B. G.; Yaman, M.; Bayrakdar, Ali; Atalar, O. (Ecole Nationale Veterinaire Toulouse, 2007)
The expression of gonadotropin-releasing hormone (GnRH) was investigated in porcupine (Hystrix cristata, n = 5) pancreas by immunohistochemistry. The GnRH immunoreactive cells were exclusively distributed into glandular structures of the exocrine pancreas with a relative high frequency (mean +/- S.D.: 63.8 +/- 1.4 cells / microscopic field). By contrast, no GnRH positive cell was evidenced in pancreatic islets. These results show that GnRH is produced by exocrine pancreas of porcupine, suggesting that this hormone could be involved in the regulation of digestion.
Keywords: gonadotropin-releasing hormone; porcupine; pancreas; immunohistochemistry